EVALUASI SISTEM PENGUPAHAN PADA PT DELTA MERLIN DUNIA TEXTILE IV BOYOLALI - Muhammad Rofiq Sunarko, Dimas Probo Santoso, Bambang Widarno & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2016)
This study aimed to evaluate the wage system in PT Delta Merlin Dunia Textile IV Boyolali. This research is descriptive research with case study method. This study did four stages in the evaluation systems of remuneration on PT Delta Merlin Dunia Textile IV Boyolali namely: describe the documents and procedures of wages, explaining the policy calculation of wages, analyze the internal control procedures of wage and analyze the report format of wages. The results we concluded that the description of documents and procedures wages in PT Delta Merlin Dunia Textile IV Boyolali show their weaknesses. Calculation of remuneration policy at PT Delta Merlin Dunia Textile IV Boyolali goes well, there are internal controls that are susceptible to fraud. Format wage statements made short by displaying the details of the average employee wage reception current month and the previous month, details of participants BPJS Kesehatan dan BPJS Ketenagakerjaan, and the details of cuts in wages of employees per unit.Keywords: evaluation, system, wages